Investigation on Ultrasonic Cavitation Erosion Behaviors of Al and Al-5Ti Alloys in the Distilled Water - Jingtao Zhao (Metals, 2020)
Al and Al-5Ti alloys were manufactured by an ultrasonic casting method with a new device, and their ultrasonic cavitation erosion behaviors of Al and Al-5Ti alloys in the distilled water were clarified. The damage mechanism was analyzed by macro photograph, scanning electronic micrograph and three-dimensional morphology, and the results demonstrate that Al-5Ti alloys have better cavitation erosion resistance than Al in terms of the mass loss and the surface damage. The deformation mechanism of Al and Al-5Ti alloys under cavitation erosion is mainly dislocation slip, and the Al3Ti phase enhances the cavitation erosion resistance of Al-5Ti alloys. In addition, the maximum depth of cavitation pits in the Al-5Ti sample is less than that in the Al sample for 31.3%.